Psychosocial Predictors of Postpartum Posttraumatic Stress Disorder in Women With a Traumatic Childbirth Experience - van Heumen, Mark A.; Hollander, Martine H.; van Pampus, Maria G.; van Dillen, Jeroen; Stramrood, Claire A. I. (Frontiers in Psychiatry, 2018)
Objective To analyze the predictive value of antepartum vulnerability factors, such as social support, coping, history of psychiatric disease and fear of childbirth, and intrapartum events on the development of symptoms of postpartum posttraumatic stress disorder (PP-PTSD) in women with a traumatic childbirth experience. Materials and methods Women with at least one self-reported traumatic childbirth experience in or after 2005 were invited to participate through various social media platforms in March 2016. They completed a 35-item questionnaire including validated screening instruments for PTSD (PTSD Symptom Checklist, PCL-5), social support (Oslo social support scale, OSS-3) and coping (Antonovsky’s sense of coherence scale, SoC). Results Of the 1599 women who completed the questionnaire, 17.4% met the diagnostic criteria for current PTSD according to the DSM-5, and another 26.0% recognized the symptoms from a previous period, related to giving birth. Twenty-six percent of the participating women had received one or more psychiatric diagnoses at some point in their life, and five percent of all women had been diagnosed with PTSD prior to their traumatic childbirth experience. Women with poor (OR=15.320, CI=8.001-29.336), or moderate (OR=3.208, CI=1.625-6.333) coping skills were more likely to report PP-PTSD symptoms than women with good coping skills. Low social support was significantly predictive for current PP-PTSD symptoms compared to high social support (OR=5.557, CI=2.967- 7.785). A predictive model which could differentiate between women fulfilling vs. not fulfilling the symptom criteria for PTSD had a sensitivity of 80.8% and specificity of 62.6% with an accuracy of 66.5%. Conclusions Low social support, poor coping, experiencing ‘threatened death’ and experiencing ‘actual or threatened injury to the baby’ were the four significant factors in the predictive model for women with a traumatic childbirth experience to be at risk of developing PP-PTSD. Further research should investigate the effects of interventions aimed at the prevention of PP-PTSD by strengthening coping skills and increasing social support, especially in women at increased risk of unfavorable obstetrical outcomes.